Fusarium oxysporum and Colletotrichum musae Associated with Wilt Disease of Coffea arabica in Coffee Gardens in Saudi Arabia - Zarraq AL-Faifi; Wail Alsolami; Emad Abada; Habib Khemira; Ghaliah Almalki; Yosra Modafer (Canadian Journal of Infectious Diseases and Medical Microbiology)
This study aimed to identify if Fusarium and Colletotrichum species are linked to coffee leaf wilt symptoms (Coffea arabica L.) gardens in Jazan region, Kingdom Saudi Arabia. The symptomatic wilted leaves and shoots were collected from Jazan Mountain Region Development Authority (JMRDA) farm in jabal Fifa. Samples of roots and leaves tissues were plated on Dox’ Agar medium and incubated for one week at 24oC. Two morphologically different fungus colonies grew on the medium. A PCR-based method was used for the molecular amplification and characterization of the fungi using a 18SrRNA specific primer. 1323 and 1501 bp PCR products were obtained by using the 1% agarose gel electrophoresis. The sequence analysis and genbank homology revealed that the present fungi were Fusarium oxysporum and Colletotrichum musae with 99 and 98% similarity, respectively. Both fungi sequences were submitted to the genebank under accession numbers OP010081 and OP010082, respectively. This is the first report of these two genera of fungi infecting the roots and leaves of coffee trees in Jazan Region of Saudi Arabia and suggests that other fungus species may play a significant role as diseases in other coffee-producing areas.